3-D X-Ray-Induced Acoustic Computed Tomography With a Spherical Array: A Simulation Study on Bone Imaging - Li, Yang; Samant, Pratik; Wang, Siqi; Behrooz, A.; Li, Dengwang; Xiang, Liangzhong (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2020)
X-ray-induced acoustic computed tomography (XACT) is a promising imaging modality combining high X-ray absorption contrast with the 3-D propagation advantages provided by high-resolution ultrasound waves. The purpose of this study was to optimize the configuration of a 3-D XACT imaging system for bone imaging. A 280 ultrasonic sensors with peak frequency of 10 MHz was designed to distribute on a spherical surface to optimize the 3-D volumetric imaging capability. We performed both theoretical calculations and simulations of this optimized XACT imaging configuration on a mouse-sized digital phantom containing various X-ray absorption coefficients. Iteration algorithm based on total variation has been used for 3-D XACT image reconstruction. The spatial resolution of imaging was estimated to about 130~μ \text{m} along both axial and lateral directions. We simulate XACT imaging of bone microstructures using digital phantoms generated from micro-CT images of real biological samples, showing that XACT imaging can provide high-resolution imaging of the mouse paw. Results of this study will greatly enhance the potential of XACT imaging in the evaluation of bone diseases for future clinical use.